Travitonics: using travertines in active fault studies - Hancock, P.L; Chalmers, R.M.L; Altunel, E.; Çakir, Z. (Elsevier BV, 1999)
Abstract Late Quaternary travertines deposited from hot springs can reveal much about the neotectonic attributes and histories of structures. On the basis of field studies in the Aegean region (Turkey and Greece), the northern Apennines (Italy) and the Basin and Range province (USA) we conclude that the following relationships are of predictive value: (i) travertine deposits are preferentially located along fracture traces, either immediately above extensional fissures or in the hanging walls of normal faults; (ii) the locations of many travertine fissure-ridge deposits coincide with step-over zones (relay ramps) between fault segments; networks of intersecting tensional fissures reflecting the complex strains experienced in such settings are probably responsible for enhancing hydrothermal flow; (iii) the morphology of travertine deposits overlying extensional fissures is controlled by the rheology of the underlying materials; tufa cones (towers, pinnacles) form on former and present lake floors where fissures underlie unconsolidated sediments, whereas fissure-ridges develop where fissures cut bedrocks at the surface; (iv) fissure-ridges comprise outwardly dipping bedded travertine flanking a central tensional fissure filled by vertically banded travertines; fissures can be used to infer local stretching directions; (v) where there are travertines datable by the U-series method it is possible to calculate time-averaged dilation and lateral propagation rates for individual fissures; (vi) most fissures cutting fissure-ridges comprise self-similar angular segments with fractal dimensions in the range 1.00–1.12, the properties of bedded travertine combined with stress perturbations at fissure tips probably being responsible for such similar fractal dimensions being inferred from such a wide range of locations. Fissures gradually increasing in width with depth are products of continuous fracture dilation in contrast to those that form during episodic dilation which display stepped increases of width with depth; (vii) travertine deposited from springs along fault zones accumulate in terraced-mounds sited down slope of the spring line; (viii) many post-depositional fractures cutting travertine deposits are locally oriented at right angles to deposit margins; and (ix) systematic joints in travertines are restricted to those parts of eroded sheet deposits that have been exhumed.